Efisiensi dan Efektivitas Pengelolaan Dana Zakat pada Baznas Provinsi Jawa Barat Menggunakan Data Envelopment Analysis dan Zakat Core Principles: Allocation to Collection Ratio - Rachmawati, Audia Kirani; Tamara, Destian Arshad Darulmalshah; Laksana, Banter; Djuwarsa, Tjetjep (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
This final project examines the efficiency and effectiveness of zakat fund management at BAZNAS West Java for the period 2015 - 2021. The method used in measuring the level of efficiency is the Data Envelopment Analysis model of Constant Return to Scale and Variable Return to Scale with Banxia Frontier. While the method used to measure the level of effectiveness is Zakat Core Principles: Allocation to Collection Ratio with Microsoft Excel. Based on the DEA CRS model, imperfect efficiency values in 2019 and 2021 are 92.5% and 62.9%. As for the results of the analysis based on the DEA VRS model, the perfect efficiency value in all periods of the study year was 100.0%. For the results of the effectiveness calculation, it produces an ACR value of 73% - 98% which is included very effective categories. Whereas the ZTR ratio is 0.36 which is included in the bad category.